Web-based athlete data processing information system at Indonesian National Sports Committee (INSC) Southwest Papua - Setyawan, Ahmad Syafei Anggun; Ramadhani, Indri Anugrah; Firman, Firman; Sahidi, Sahidi (Jurnal Ilmu Keolahragaan, 2025)
Background. The current development of information technology requires organizations in various fields, including sports, to have an information system capable of presenting data accurately, quickly, and relevantly. At the Indonesian National Sports Committee (INSC) of Southwest Papua, the process of processing athlete data is still done manually using printed documents and Microsoft Word and Excel files. This method causes various obstacles, including slow input processes, high risk of recording errors, and delays in report generation. These problems have an impact on the effectiveness of the organization in managing and monitoring athlete data. Objectives. This study aims to design and develop a web-based athlete data processing information system that can improve efficiency, accuracy, and speed of data access. Methods. The research method uses the Waterfall software development model, with system design using Unified Modeling Language (UML), PHP programming language, and MySQL database. The subjects of this study were athlete data registered with the Indonesian National Sports Committee (INSC) Southwest Papua. The data includes athletes' personal identities, sports disciplines , achievement histories, and other administrative information used in the coaching and evaluation processes. System testing was conducted to ensure functionality suitability with organizational needs. Results. The results of the study show that the web-based information system that was built can automate the process of inputting, storing, and reporting athlete data in a more structured manner. This system has been proven to speed up the data processing process, minimize potential errors, and support information transparency. Conclusion. Thus, this research contributes to the development of information technology in the field of sports, particularly in the management of athlete data at the regional level. The implementation of this system is expected to improve the administrative performance of INSC Southwest Papua and serve as a model for the implementation of similar systems for other sports organizations in Indonesia.